FINANCIAL ENGINEERING OR ETHICAL DILEMMA, LITERATURE REVIEW ON PROFIT MANAGEMENT - Ismiantika; Rizal, Noviansyah; Heni; Rahmawati, Febriane Devi (Sekolah tinggi ilmu ekonomi pemuda, 2024)
Earnings management can also directly impact the quality of financial information presented in reports. Inappropriate accounting policy choices or unreasonable adjustments can affect fundamental analysis by investors and financial analysts. The objective of this research is to determine how financial engineering practices contribute to the formulation and implementation of earnings management policies in a company's financial reports, and what their impact is on the reliability of financial information presented to stakeholders. The research also aims to understand the ethical dilemmas associated with financial engineering practices and earnings management as reflected in the literature review. In the literature review structure of this study, a systematic approach is applied to conduct a literature review. The literature selection process begins with determining keywords relevant to the research scope, including terms such as